2020
DOI: 10.31234/osf.io/gqyuj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Faculty Subjective Well-being: An Achievement Goal Approach

Abstract: Research suggests that higher education teachers worldwide experience high levels of stress, burnout, and other adverse experiences due to the challenging nature of their work. To better understand why, under similar conditions, some teachers struggle while others flourish, studies are needed which recognize multiple facets of their subjective well-being (SWB) and explain differences therein using comprehensive theoretical frameworks. From an achievement goal perspective, goals can be expected to underlie diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In line with this, studies have consistently found positive links between mastery approach goals and aspects of SWB in teaching populations, including positive emotions, job satisfaction, personal accomplishment, and interest (e.g., Janke et al, 2019;Mascret et al, 2015;Papaioannou & Christodoulidis, 2007;Retelsdorf et al, 2010;Tönjes et al, 2008). In terms of further differentiating mastery approach goals, positive associations with SWB have been documented both for task approach and learning approach goals, with some indications that task approach goals may be more relevant, particularly regarding emotional experiences (e.g., Daumiller et al, 2019;Rinas et al, 2022). While both goals can generally be expected to be positively associated with SWB, further research is needed to disentangle how these goals uniquely matter for different aspects of SWB in faculty.…”
Section: Mastery Approach Goalsmentioning
confidence: 90%
See 3 more Smart Citations
“…In line with this, studies have consistently found positive links between mastery approach goals and aspects of SWB in teaching populations, including positive emotions, job satisfaction, personal accomplishment, and interest (e.g., Janke et al, 2019;Mascret et al, 2015;Papaioannou & Christodoulidis, 2007;Retelsdorf et al, 2010;Tönjes et al, 2008). In terms of further differentiating mastery approach goals, positive associations with SWB have been documented both for task approach and learning approach goals, with some indications that task approach goals may be more relevant, particularly regarding emotional experiences (e.g., Daumiller et al, 2019;Rinas et al, 2022). While both goals can generally be expected to be positively associated with SWB, further research is needed to disentangle how these goals uniquely matter for different aspects of SWB in faculty.…”
Section: Mastery Approach Goalsmentioning
confidence: 90%
“…Several studies have documented positive associations between performance approach goals and aspects of SWB in teaching populations, such as pride, personal accomplishment, and job satisfaction (Rinas et al, 2020;Tönjes & Dickhäuser, 2009;Tönjes et al, 2008;Wang et al, 2018). Other studies, however, have found performance approach goals to have non statistically significant or, on occasion, adverse associations with aspects of SWB (Retelsdorf et al, 2010;Rinas et al, 2022;Wang et al, 2017). These inconsistencies may stem from studies not having clearly distinguished between appearance (focus on appearing competent to others) and normative (focus on outperforming others) components of performance approach goals; which have been found to exhibit differential effects (see Hulleman et al, 2010;Senko & Dawson, 2017;Wirthwein & Steinmayr, guished. Although theoretically relevant, their linkages with subjective well-being in faculty have been found to be rather inconclusive (see Daumiller et al, 2019;Rinas et al, 2020;Rinas et al, 2022) and were thus not analysed in the present study for reasons of parsimony.…”
Section: Performance Approach Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a bilingual online study including 1410 university instructors from Germany, the USA, and India who reported their need satisfaction, achievement goals, positive affect, self-reported teaching quality, and professional learning. As a separate research question, we also assessed multi-faceted well-being and examined its relation to achievement goals in another paper based on the same dataset (Rinas et al 2020a).…”
Section: Methodsmentioning
confidence: 99%